If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-5x + 3) + (-7x + -1) = 0 Reorder the terms: (3 + -5x) + (-7x + -1) = 0 Remove parenthesis around (3 + -5x) 3 + -5x + (-7x + -1) = 0 Reorder the terms: 3 + -5x + (-1 + -7x) = 0 Remove parenthesis around (-1 + -7x) 3 + -5x + -1 + -7x = 0 Reorder the terms: 3 + -1 + -5x + -7x = 0 Combine like terms: 3 + -1 = 2 2 + -5x + -7x = 0 Combine like terms: -5x + -7x = -12x 2 + -12x = 0 Solving 2 + -12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -12x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -12x = 0 + -2 -12x = 0 + -2 Combine like terms: 0 + -2 = -2 -12x = -2 Divide each side by '-12'. x = 0.1666666667 Simplifying x = 0.1666666667
| -2y-(0)=2y-8 | | 1-3Y=3 | | 6+25x=15x+14 | | A+5=-4a+5 | | -2x+4=-6+26x | | 55-10x=19+8x | | 5m+7n-2(6m-8n)= | | 49/(-7)=-7k/(-7) | | -2(0)+x=2(0)-8 | | 90=-4x | | x=75(x)+7 | | (6-5i)+(7-2i)= | | 42-3x=12+12x | | 441+b*b=841 | | 3b/100 | | 27-4x=12-7x | | y=5/8=-1/4 | | 11x=-35+4 | | 2(x-6)+2x-10= | | .23x=.94 | | 12y=38x-100 | | 8x-(5x-7)= | | k/12=3 | | 5m-6=8 | | 3y/100 | | 38x+12y=100 | | -8v-5=3v^2 | | 5m+6=8 | | 12x-38y=100 | | 3x/100 | | y(0)-8=2x | | 196+b*b=529 |